Linking literacy and libraries in global communities - Asselin, Marlene 1949-; Doiron, Ray (Farnham, Surrey, England Ashgate, 2013)
The authors of this book highlight the emerging role of libraries and community partners in literacy development and provide concrete examples via case studies drawn from global communities, demonstrating how libraries are working to support local literacies. They also suggest recommendations for supporting the critical role for libraries in supporting global literacies. The book will become essential reading for all those interested in literacy and libraries throughout the world.
Libraries as forces for literacy and learning -- Building a culture for reading through libraries -- Supporting learning and literacy through libraries -- Conceptual models of libraries : libraries as learning commons -- Conceptual models of libraries : the library as community learning centre -- Conceptual models of libraries : libraries as agents of social change -- Mobile libraries as effective solutions to reading access and reading promotion in remote communities -- Effective practices in reading promotion and literacy development -- An ecological framework for ongoing community library -- Development.
Includes bibliographical references and index.
Keywords: Libraries and community; Libraries and community -- Case studies; Literacy; Libraries and education; Reading promotion